Alteration of systemic and uterine endometrial immune populations in patients with endometriosis. (29th October 2020) - Le, Nhung X. H.; Loret de Mola, Julio R.; Bremer, Pamela; Groesch, Kathleen; Wilson, Teresa; Diaz‐Sylvester, Paula; Braundmeier‐Fleming, Andrea G.
Abstract: Problem: Endometriosis is defined as growth of endometrial tissue in ectopic locations; it is associated with infertility and chronic pain and affects ~12% of reproductive‐aged women. Although inflammation is known to play a key role in endometriosis, knowledge related to immune phenotypes associated with this disease is lacking. This study aimed to characterize immune profiles in patients with endometriosis, to assess inflammatory mediators, to and determine if surgical and/or hormonal therapies restore immune homeostasis. Methods of study: Samples from nine controls and 20 histologically confirmed endometriosis patients were collected upon surgery and ~1‐3 weeks post‐surgical intervention. Subjects were either not utilizing hormonal suppression or were currently on monophasic hormonal therapy. Tolerant regulatory T cells (Tregs = natural [nTregs] +inducible [iTregs]) and inflammatory T helper 17 (Th17) cells were identified in peripheral blood via flow cytometry and within the eutopic/ectopic endometrial tissues via immunohistochemistry and real‐time‐qPCR. Cytokines were assessed via 10‐plex‐ELISA. Results: Patients with endometriosis not utilizing hormonal therapy exhibited lower iTregs (tolerant), greater Th17 (inflammatory), and a reduction in Treg/Th17 ratio ( P  < .05), indicative of systemic inflammation. Treg and Th17 localizations were enhanced within the ectopic endometrial implant, which promotes lesion development. Hormonal therapy decreased systemic and local inflammation (eutopic/ectopic endometrium) via decreased iTregs and Th17 cells in patients with endometriosis ( P  < .05). Thus, imbalance within immune populations correlated with increased inflammation in patients with endometriosis, which was mitigated by hormonal therapy. Conclusions: Patients with endometriosis exhibited systemic and localized inflammation within ectopic and endometrial tissues. Hormonal therapy dampened inflammation caused by disease.